Vehicle crashworthiness performance in frontal impact: Mathematical model using elastic pendulum. (September 2022) - Noorsumar, Gulshan; Rogovchenko, Svitlana; Robbersmyr, Kjell G.; Vysochinskiy, Dmitry
Abstract: Vehicle occupant injuries due to collisions cause many fatalities every year. Safe vehicle design plays a critical role in averting serious injuries to occupants and vulnerable road users in the event of a crash. In this paper we study a full frontal vehicle crash against a rigid barrier introducing a Lumped Parameter Model (LPM) inspired by the elastic pendulum motion. The model uses polar coordinates to simplify the problem and the governing equations have been defined using Lagrangian formulation. The Simulink model has been validated against Finite Element (FE) data demonstrating good correlation with pitching angle and maximum crush of the vehicle. These parameters are crucial for designing vehicles which efficiently protect occupants. Highlights: Mathematical models of vehicle crash injury values can replace physical testing. Lumped Parameter Model inspired by the elastic pendulum motion is presented. Simulink model shows good correlation with pitching angle and maximum crush. Model is validated against finite element simulation data. Model uses Lagrangian formulation in polar coordinates to predict impact mechanics.